Diagnosis and Treatment of a Lateral Meniscal Cyst with Musculoskeletal Ultrasound - Hamilton Chen (Case Reports in Orthopedics)
Meniscal cysts are a relatively uncommon occurrence that may result in pain and disability in the knee. It is widely believed that meniscal cysts are secondary to fluid extrusion from a meniscus tear. Typically, diagnosis of a meniscal cyst typically requires magnetic resonance imaging (MRI) to delineate the cyst and any associated injuries. With improvements in sonographic technology, ultrasound has emerged as a sensitive modality for detection of meniscal cysts. We present a patient with a contraindication to MRI who was diagnosed with a lateral meniscal cyst by musculoskeletal ultrasound and treated with an ultrasound-guided lateral meniscal cyst aspiration and injection.